2017
DOI: 10.1007/s00441-017-2723-8
|View full text |Cite
|
Sign up to set email alerts
|

Cd271 mediates proliferation and differentiation of epidermal stem cells to support cutaneous burn wound healing

Abstract: Burn wounds can significantly reduce the quality of life of patients with respect to their physiology and psychology and can even threaten their lives. Many treatments have been proposed, including stem cell therapy but no effective method can as yet cure such damage. Our study highlights the role of Cd271 in epidermal stem cells (eSC) during the healing of burn wounds. The expression of Cd271 increases together with burn wound healing. Injection of Cd271-over-expressing eSC into wounds promotes the healing ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Another experiment held on murine epidermal stem cell culture revealed, that overexpression of Cd271 (p75 neurotrophin receptor) increased cell ability to differentiate, proliferate and migrate. The same study also proved, that Cd271 promotes burn wound healing on mice model (Zhang et al, 2018a). Human stem cells have also been subject to some genetic modifications.…”
Section: Genetic Modifications Of Stem Cellsmentioning
confidence: 64%
“…Another experiment held on murine epidermal stem cell culture revealed, that overexpression of Cd271 (p75 neurotrophin receptor) increased cell ability to differentiate, proliferate and migrate. The same study also proved, that Cd271 promotes burn wound healing on mice model (Zhang et al, 2018a). Human stem cells have also been subject to some genetic modifications.…”
Section: Genetic Modifications Of Stem Cellsmentioning
confidence: 64%
“…The other half of the above tissue was fixed in 10% formalin solution, embedded in paraffin and sectioned at 3 μm for histochemical analyses which were performed by haematoxylin–eosin (H&E) staining and immunohistochemical (IHC) staining. Deparaffinization, rehydration, antigen retrieval, endogenous peroxidase blocking, and goat serum (#SP-9001; ZSGB-BIO, Beijing, China) blocking of paraffin sections were performed as previously described [ 33 35 ]. Next, the wound skin tissue sections were incubated with primary antibody against RAMP1 (#ab156575; Abcam Plc, Cambridge, UK) at a dilution of 1:200 at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The researchers investigated the kinetic movement of p75NTR + SSCs in wound healing and found that the protein level of p75NTR in the epidermis was decreased at an early stage but increased promptly in the mid to late stages of the burn wound healing process, suggesting that p75NTR was involved in the re-epithelialization and remodeling of the epidermis in the mid-to-late stages. 119 Moreover, Iwata et al confirmed that p75NTR + SSCs proliferated and migrated to the sites of damage from 3 days after wounding and that the expression of TGFβ2, VEGFα, FGF2, EGF, PDGFB, and TGFβ1 in P75NTR + SSCs was higher than that in p75NTR − SSCs, indicating that the effect of p75NTR + SSCs on wound healing was achieved through not only differentiation but also paracrine action. 120…”
Section: Skin-derived Mscsmentioning
confidence: 98%